ANALYSIS OF YOUTH POLITICAL WORLDVIEWS TOWARDS THE THAI GOVERNMENT IN 2020 - Bhalakula, Anucha (Journal of MCU Phetchaburi Review, 2021)
Democracy values ​​the principle of sovereignty, freedom, equality, rule of law, majority principle. Which must be stipulated in the constitution as a joint agreement The government sheet services in 2020 are very inefficient. The youths protested the eviction with the proposal that Stop the threat of civil liberties Open the way for amendments to the 2017 constitution and request the dissolution of the parliament for new elections. Which is the time when the COVID-19 epidemic It spreads the infection quickly without effective drugs. It affects the lifestyles and occupations of all citizens. It reflects the lack of transparency in the government. Some ministers and government officials have no integrity in the performance of their duties. All were reflected in social aspects such as increased crime. More and more drugs young people have easy access to medicines. Economically, companies and factories have announced closures. There were many layoffs. As a result, hundreds of thousands of people lost their jobs immediately. Many types of working-age people have returned to their domiciles. Politics has resulted in the elimination of conflicting opinions, which violates the law announced by the government. Some scholars argue that It was another era of Thailand’s military dictatorship. Religious, the government conducted the arrest of several elderly monks. Which is accused of being involved in a temple subsidy corruption case, Including the prosecution of monks and novices who went out to join the march to oust the government both in violation of the rules and regulations in terms of transparency and accountability of the government It was seen as dishonest in the performance of the duties of some ministers and government officials. Even if there is a fault was not punished according to the absolute offense but to protect them from guilt or received a light punishment